Lightweight Design of Six-dof Tandem Manipulator Based on Additive Manufacturing Technology. (October 2019) - Lv, Xin; Yang, Yongtai; Zeng, Wenhao; Xu, Dawei
Abstract: At present, topological optimization represents the most advanced structural design technology, and additive manufacturing represents the most advanced manufacturing technology. Combining the two technologies to provide a very effective way for the lightweight of the manipulator arm. Taking the six-degree-of-freedom series manipulator as the object, the lightweight design was carried out from the aspects of material lightweight and structure lightweight. Firstly, under the limit conditions, the exploratory topology optimization of the manipulator arm of the aluminum alloy material and the manipulator arm of the 3D printed plastic material was carried out respectively, and the optimization results were compared. 3D printing plastic material was selected as the design material of the manipulator. Then, under the condition that the stiffness and strength requirements are met, the manipulator of 3D printing plastic material is designed with the method of size optimization and topology optimization for the two limit working conditions, and the geometric reconstruction and simulation verification are carried out at last. The results show that the final manipulator arm meets the requirements of stiffness and strength, reduces the weight by 26.5%, and finally achieves the goal of lightweight.